Mid-infrared vibrational study of deuterium-containing PAH variants. (15th November 2016) - Buragohain, Mridusmita; Pathak, Amit; Sarre, Peter; Onaka, Takashi; Sakon, Itsuki
Abstract: Polycyclic Aromatic Hydrocarbon (PAH) molecules have been long proposed to be a major carrier of 'Unidentified Infrared' (UIR) emission bands that have been observed ubiquitously in various astrophysical environments. These molecules can potentially be an efficient reservoir of deuterium. Once the infrared properties of the deuterium-containing PAHs are well understood both experimentally and theoretically, the interstellar UIR bands can be used as a valuable tool to infer the cause of the deuterium depletion in the ISM. Density Functional Theory (DFT) calculations have been carried out on deuterium-containing ovalene variants to study the infrared properties of these molecules. These include deuterated ovalene, cationic deuterated ovalene, deuteronated ovalene and deuterated-deuteronated ovalene. We present a D/H ratio calculated from our theoretical study to compare with the observationally proposed D/H ratio. Abstract : Highlights: DFT has been used to study the infrared properties of interstellar PAH molecules. An emission model is used to obtain the emission spectrum of PAH molecules. Deuteration has been considered in all the unique sites of the ovalene molecule. Relative intensities and scaled frequencies are used to plot a Gaussian. Normalization has been made same across all the species.